FIRM SIZE MEMODERASI PENGARUH FINANCIAL RATIO DAN FIRM AGE TERHADAP FIRM VALUE - Angelica Suciadi; Yanti Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
This study aims to find out how the effect of financial ratios and company age on company value, and the effect of company size on company value in the consumer cyclical sector listed on the Indonesia Stock Exchange during 2017-2021. The sample was selected by purposive sampling method and the valid data are 63 companies. The data processing technique uses multiple regression analysis and moderated regression analysis assisted by the Eviews program version 12 and Microsoft Excel 2013. The results of this study indicate that leverage has a positive effect on firm value, liquidity and firm age has a negative effect on firm value, and profitability, activity, and firm size do not effect on firm value. Based on the results of the moderation test, firm size can moderate the effect of profitability, leverage, activity, and firm age on firm value. However, firm size cannot moderate the effect of liquidity on firm value. The implication in this study is the need for more optimal management performance in managing the company so that it can provide a positive signal for investors which is reflected in the financial statements.